A STUDY OF SELF-CONCEPT IN RELATION TO ACADEMIC ACHIEVEMENT AMONG 9TH STANDARD STUDENT - K, Murugan; Jebaraj, Justin (International Journal of Research -GRANTHAALAYAH, 2017)
The specific needs for classifying these spectacles of self-concept in relation to academic achievement as a usual and predictable vital result of student growth and development rather than among compulsive symptom. The self-concept in relation to academic achievement turn out to be important in the actions of individuals. As the students are the stakes of the future generations their significance pattern of self-concept in relation to academic achievement are vital. So the present study intends to measure a study of self-concept in relation to academic achievement among 9th standard student. The investigator adopted survey method to study the self-concept between 9th standard students from selected government, private and aided school. For this study a sample of 220 students taken from five various schools which are situated in Coimbatore district selected by the investigator using simple random sampling technique.